2016
DOI: 10.18632/oncotarget.10573
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 is an atypical intestinal tumor suppressor controlling the oncogenic Wnt/ß-catenin signaling

Abstract: SOX9 inactivation is frequent in colorectal cancer (CRC) due to SOX9 gene mutations and/or to ectopic expression of MiniSOX9, a dominant negative inhibitor of SOX9. In the present study, we report a heterozygous L142P inactivating mutation of SOX9 in the DLD-1 CRC cell line and we demonstrate that the conditional expression of a wild type SOX9 in this cell line inhibits cell growth, clonal capacity and colonosphere formation while decreasing both the activity of the oncogenic Wnt/ß-catenin signaling pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 37 publications
6
64
0
Order By: Relevance
“…Moreover, miR-101-3p targets SOX9 which bridges the pathway to Wnt/β-catenin. Several studies in different types of cancer showed the connection between SOX9 and the Wnt/β-catenin [72][73][74]. As a result, the oncogenic lncRNAs NEAT1 promotes NSCLC progression by activating the miR-101-3p/SOX9/Wnt/β-catenin axis.…”
Section: The Pi3k/akt Pathwaymentioning
confidence: 99%
“…Moreover, miR-101-3p targets SOX9 which bridges the pathway to Wnt/β-catenin. Several studies in different types of cancer showed the connection between SOX9 and the Wnt/β-catenin [72][73][74]. As a result, the oncogenic lncRNAs NEAT1 promotes NSCLC progression by activating the miR-101-3p/SOX9/Wnt/β-catenin axis.…”
Section: The Pi3k/akt Pathwaymentioning
confidence: 99%
“…As an atypical tumor suppressor, SOX9 has been shown to interact with nuclear β-catenin. Inactivation of SOX9 causes loss of inhibition of the oncogenic Wnt/β-catenin signalling pathway and is associated with patient survivals (54). Some novel TSGs harbor mutational hotspots.…”
Section: Application To Tcga Datamentioning
confidence: 99%
“…Although most studies showed that SOX9 played an oncogenic role in cancer development. Excopic expression of SOX9 was found to suppress cell growth, clonal capacity and colonosphere formation by inhibiting Wnt/ß-catenin signaling pathway and c-myc expression in colorectal cancer, suggesting that SOX9 might be a tumor suppressor in colorectal cancer [81]. SOX9 expression was progressively decreased in cervical carcinoma in situ and especially in invasive cervical carcinoma, compared with normal cervix tissue.…”
Section: Sox9 and Cancermentioning
confidence: 96%